2019
DOI: 10.1111/1467-8578.12254
|View full text |Cite
|
Sign up to set email alerts
|

Supporting a child with dyslexia: how parents/carers engage with school‐based support for their children

Abstract: Parents’/carers’ experiences of their children’s dyslexia were explored in a mainstream secondary school in England. Interviews were undertaken with the parents/carers of young people at Hilltop View School, a secondary school in south‐west England. Bourdieusian concepts of field, habitus and practice were powerful in underpinning analysis using Jenkins’s (2008) ‘levels of interaction’ when exploring these experiences. It was found that parents/carers drew on bio‐social conceptualisations when making sense of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(36 citation statements)
references
References 21 publications
0
36
0
Order By: Relevance
“…This is also problematic, as there is potential for individuals to understand reasons for their difficulties as being outside of their control, leading to disempowerment and oppression when they experience dyslexic-type difficulties. As such this paper draws on a bio-social model of dyslexia congruent with earlier work by MacDonald [22] and Ross [11,15]. This model allows for consideration of underlying impairments within the individual, and external, social factors which act to emphasize or minimize effects of that underlying impairment.…”
Section: Dyslexia: What Is It?mentioning
confidence: 97%
See 4 more Smart Citations
“…This is also problematic, as there is potential for individuals to understand reasons for their difficulties as being outside of their control, leading to disempowerment and oppression when they experience dyslexic-type difficulties. As such this paper draws on a bio-social model of dyslexia congruent with earlier work by MacDonald [22] and Ross [11,15]. This model allows for consideration of underlying impairments within the individual, and external, social factors which act to emphasize or minimize effects of that underlying impairment.…”
Section: Dyslexia: What Is It?mentioning
confidence: 97%
“…Medicalized views of dyslexia locate its root causes within the individual with little-to-no reference to structural factors affecting it [19]. Solvang [20], Ross [15] and Calfee [19] found that language surrounding 'diagnosis' of dyslexia frame it as an internal 'impairment' within the individual. This serves to explain why children experienced difficulties and removes parents' 'fault' for their children's dyslexic difficulties.…”
Section: Dyslexia: What Is It?mentioning
confidence: 99%
See 3 more Smart Citations